Proposta de gestão de processos para uma empresa de embalagens - Conto, Angela Gabriela de (2019)
The present study aimed to analyze the processes of the Alfa Embalagens Company, with a view to achieving greater efficiency in its actions, in order to make it more competitive. For that, the qualitative approach was used, through a case study, bibliographic survey, exploratory and documentary research, and non-participant observation. The tools used to carry out the intervention in the study were SWOT analysis and GUT matrix to understand the current situation of the company, the Balanced Scorecard to suggest the monitoring of performance indicators in the organization, and the tool 5W2H to develop the action plan for the implementation of process management. The sequence of steps for the implementation of the process management followed the model GEPRO (management by processes) elaborated by UNICAMP. Through the application of the present study we sought as result to help the company to develop in the competitive environment by mapping and remodeling its organizational processes, also collaborating with society in the generation of jobs.